Systemic review and meta‐analysis of the association between interleukin‐10 and Takayasu arteritis - Zhou, Hang; Zhou, Boyang; Liang, Surong; Zhao, Jian (International journal of rheumatic diseases, 2023)
Objective The aim of this meta‐analysis is to investigate the relationship between interleukin (IL)‐10 levels and its polymorphism and Takayasu arteritis (TAK). Methods Five databases including PubMed, Web of Science, Ovid, Sinomed and China National Knowledge Infrastructure (CNKI) were gone through from inception to March 31, 2022. Studies were screened according to the inclusion and exclusion criteria. Newcastle‐Ottawa Scale (NOS) was applied to assess study quality. Strengths of association were evaluated by odds ratio (OR) and 95% CI. The T v. t (allele contrast), TT v. tt (homozygous contrast), Tt vs tt (heterozygous contrast), TT + Tt vs tt (dominant contrast) and TT vs Tt + tt (recessive contrast) models were adopted. Results Seven studies were included. No significant relationship between IL‐10 and TAK was detected in the included patients (P > 0.05). The levels of IL‐10 were lower in the active group than those in the stable group, which was −0.47 (95% CI: −0.93, 0.00) (P = 0.05). No significant relationships between IL‐10 and TAK were found under all contrasts for polymorphisms rs1800871, rs1800872 and rs1800896 (P > 0.05). Conclusions There was no significant difference in IL‐10 levels between TAK patients and control subjects. The levels of IL‐10 were lower in TAK patients in the active stage. There was no significant association between IL‐10 gene polymorphisms and TAK. Further well‐designed studies with larger sample sizes in patients with different stages are needed.